The IMPLEMENTATION OF HALAL PRODUCT GUARANTEE POLICY IN INDONESIA - Dwijaya, Ananda Gymnastiar; Harmono, Harmono; Harliyanto, Rois (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2024)
The implementation of Halal Product Guarantee in Indonesia has been in effect since the new order period and currently the regulation of halal certification is regulated in Law Number 33 of 2014 concerning Halal Product Guarantee. This study aims to determine the legal aspects of community compliance with mandatory halal and to find out what are the challenges and obstacles in the implementation of halal product guarantees. The method used in this research is descriptive qualitative method (Normative Empirical). The results of this study indicate that the public has begun to be aware of the mandatory halal policy, but there are still several obstacles such as the lack of socialization related to understanding the mandatory halal itself, miscommunication between parties, obstacles to certification of slaughter animal products, therefore stakeholders (Government and related institutions) must be more vigorous in educating the public about the importance of halal certification, because indeed this halal certification aims to protect the public (consumers) from products that are not halal.